Prospects For The Development of Electronic Trade Processes Based on Local Characteristics - Soliev Bakhromjon Nabijonovich; Rasulov Akbarali Mahamatovich (International Journal on Orange Technologies, 2021)
The article presents the opportunities and prospects of the digital economy and the factors that determine them. Information was provided on the software part and additional programs in the organization of e-commerce processes